The Contribution of Phospholipase C in Vomiting in the Least Shrew (Cryptotis Parva) Model of Emesis - Zhong, Weixia; Darmani, Nissar A. (Frontiers in Pharmacology, 2021)
Gq and Gβγ protein-dependent phospholipase C (PLC) activation is extensively involved in G protein-coupled receptor (GPCR)-mediated signaling pathways which are implicated in a wide range of physiological and pathological events. Stimulation of several GPCRs, such as substance P neurokinin 1-, dopamine D2/3-, histamine H1- and mu-opioid receptors, can lead to vomiting. The aim of this study was to investigate the role of PLC in vomiting through assessment of the emetic potential of a PLC activator (m-3M3FBS), and the antiemetic efficacy of a PLC inhibitor (U73122), in the least shrew model of vomiting. We find that a 50 mg/kg (i.p.) dose of m-3M3FBS induces vomiting in ~90% of tested least shrews, which was accompanied by significant increases in c-Fos expression and ERK1/2 phosphorylation in the shrew brainstem dorsal vagal complex, indicating activation of brainstem emetic nuclei in m-3M3FBS-evoked emesis. The m-3M3FBS-evoked vomiting was reduced by pretreatment with diverse antiemetics including the antagonists/inhibitors of: PLC (U73122), L-type Ca2+ channel (nifedipine), IP3R (2-APB), RyR receptor (dantrolene), ERK1/2 (U0126), PKC (GF109203X), the serotoninergic type 3 receptor (palonosetron), and neurokinin 1 receptor (netupitant). In addition, the PLC inhibitor U73122 displayed broad-spectrum antiemetic effects against diverse emetogens, including the selective agonists of serotonin type 3 (2-Methyl-5-HT)-, neurokinin 1 receptor (GR73632), dopamine D2/3 (quinpirole)-, and muscarinic M1 (McN-A-343) receptors, the L-type Ca2+ channel (FPL64176), and the sarco/endoplasmic reticulum Ca2+-ATPase inhibitor thapsigargin. In sum, PLC activation contributes to emesis, whereas PLC inhibition suppresses vomiting evoked by diverse emetogens.